PENGARUHPEMBERIAN PAKAN DENGAN LEVEL PROTEIN YANG BERBEDA TERHADAP ENERGI METABOLISME AYAM KAMPUNG - Erik Priyo Santoso; Eka Fitasari (Universitas Tribhuwana Tunggadewi, 2016)
The purpose of this research is to determine the level of protein stage that gives the best results against the metabolizable energy of Local Chickens. The results of this research are expected can be a consideration and information about the differences effect of the dietary protein provision to the digestibility of metabolizable energy in Local Chicken, especially in the